Comparative proximate composition and cyanide contents of each parts of local cassava (Manihot esculenta Crantz) - Idris, Sarah; Shamsudin, Rosnah; Mokhtar, Mohd Noriznan; Mohd Nor, Mohd Zuhair; Abd Gani, Siti Salwa (Malaysian Society of Agricultural Engineers, 2019)
Each cassava parts, namely tuber, discarded tuber, leaves, stems, inner and outer peels of yellow cassava (Manihot esculenta Crantz) from Selangor, Malaysia were used in this study. The cassava plant portions such as the tubers, stems, peels, discarded tuber, and leaves were 50.06%,31.01%, 10.63%, 6.92 and 1.49% (w/w) respectively. Proximate analysis show that all the cassava parts had high dry matter content with stems had the highest dry matter (98.77±0.00) than other parts and the leaves had the least (93.89±0.06). There were significant differences (p<0.05) in crude protein, crude fat, crude fiber, ash, and carbohydrate. The leaves had the highest crude protein (28.02±0.10), crude fat (5.63± 0.12) and gross energy (4824.3 g/cal). Stems had the highest crude fiber (39.51±0.05), outer peels have the highest ash (14.59± 0.07) and tuber had the highest carbohydrates(92.66± 1.88) compared to other parts. All parts were observed to had no significant difference and have very low cyanide content (p>0.05). These results indicate that the leaves and the stems contained nutrients which can be included in the diet of animal after proper processing techniques that can lowering the cyanide content to the safe level.